Genetic variability for seed nutritional composition in pearl millet genotypes analyzed by biplot method (Revista de Investigaciones Universidad del Quindío, 2023)
This study evaluated the chemical composition of pearl millet seeds belonging to different genotypes by biplot analysis. Seeds of 26 different pearl millet populations obtained from ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) within the scope of TÜBİTAK 219O103 run by Şırnak University were used. The seeds were ground and analyzed for their chemical composition, i.e., acid detergent fiber (ADF), neutral detergent fiber (NDF), crude protein (CP), digestible dry matter (DDM) and dry matter intake (DMI) rate. The results revealed that crude protein ratio varied between 11.74-19.24%, whereas ADF ratio differed between 3.44-11.43%. Similarly, NDF ratio varied between 10.23-23.47%, while DDM ratio ranged between 79.98-86.21%. Likewise, DMI ratio differed between 5.11-11.72%. Scatter plot obtained after biplot analysis indicated three different groups based on the analyzed traits. The first group contained DDM and DMI, whereas the second group consisted of ADF and NDF. The protein ratio was in the third group. It was determined that ADF-NDF and DMI-DDM properties were negatively correlated with each other. According to biplot, genotypes ‘A5-13’, ‘A13-6’ and ‘B1-7’ were prominent for ADF -NDF, DMI-DDM, and protein ratio, respectively. Therefore, these genotypes can be used in future studies to induce the desired traits.
Keywords: Pearl millet; genotypes; biplot; chemical composition